Arabic Language Immersion Models in Indonesian Islamic Universities: A Phenomenological Multi-Campus Study - Nuraini, Nuraini; Setyawan, Cahya Edi; Hanun, Aisyatul; Rauhillah, Siti; Alribdi, Nada Ibrahim (Ta’lim al-’Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
Arabic language immersion has been widely recognized as an effective approach to second language acquisition; however, its implementation in Islamic higher education remains underexplored, particularly within culturally specific contexts like Indonesia. This study aims to explore and conceptualize a contextually grounded model of Arabic language immersion in Indonesian Islamic universities through a phenomenological lens. Research was conducted at three prominent institutions with established Arabic programs: UIN Sunan Kalijaga, University of Darussalam Gontor, and Ar-Raayah College of Arabic Language in Sukabumi. A total of 18 participants—including instructors, curriculum developers, and students—were selected through purposive sampling. Data were collected via in-depth interviews, participant observation, and documentation, and analyzed using thematic analysis to uncover patterns from participants’ lived experiences. The findings reveal that effective immersion is structured around four interrelated components: (1) an integrated and spiral curriculum, (2) intensive Arabic-only environments, (3) religious-cultural contextualization through Islamic practices, and (4) sustained institutional support. These elements form a holistic immersion framework that aligns linguistic competence with Islamic educational values. The study contributes to the theoretical discourse on language immersion by offering a culturally embedded model. It provides practical guidance for Islamic institutions aiming to enhance Arabic programs through authentic, pedagogically coherent strategies.